ON THE WAY TO YOURSELF. REVIEW OF THE BOOK OF TURCHENKO F. G. FROM THE CHALLENGES OF THE ERA. MEMOIRS OF A HISTORIAN. ZAPORIZHZHYA: PUBLISHING HOUSE "HELVETICA", 2023. 400 P. (Південний архів (історичні науки), 2025)
ON THE WAY TO YOURSELF. REVIEW OF THE BOOK OF TURCHENKO F. G. FROM THE CHALLENGES OF THE ERA. MEMOIRS OF A HISTORIAN. ZAPORIZHZHYA: PUBLISHING HOUSE "HELVETICA", 2023. 400 P.